Analysis of relationships between monetary policy and balance of payments according to the monetary approach in Turkey (1990-2000) - CÖMERTLER ŞİMŞİR, Necmiye (Turkish Economic Review, 2018)
Abstract. One of the main objectives of an economic policy is to keep balance of payments in equilibrium. For this purpose, a number of approaches have been developed. In this study, by assesing alternative approaches, it is tried to analyse the relationship between the balance of payments and monetary parameters in Turkey. As far as the monetary approach is concerned, the study results found a close relationship between applied monetary policies and balance of payments in Turkey case. Keywords. Balance of payments, Monetary approach, Monetary policy. JEL. F30, E42,E52.